The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1080/01904169409364717
|View full text |Cite
|
Sign up to set email alerts
|

A humic acid improves growth of tomato seedling in solution culture

Abstract: The effects of humic acid (HA) on nutrient accumulation and growth of tomato seedlings were evaluated in a solution of limited nutrient availability in a greenhouse. HA additions were made to the nutrient solution at rates of 0, 640, 1280, or 2560 mg/L. The addition of 1280 mg/L HA produced significant increases in shoot accumulation of P, K, Ca, Mg, Fe, Mn, and Zn as well as increased accumulation of N, Ca, Fe, Zn, and Cu in roots. Fresh and dry weights of roots were also increased, However, on comparing nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
75
1
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 12 publications
24
75
1
6
Order By: Relevance
“…As substâncias húmicas presentes na solução em dosagem mais elevadas apresentaram mais ligantes que os íons metálicos presentes na solução para poderem ser complexados e se tornarem menos disponíveis para as raízes das plantas, inibindo o desenvolvimento das mesmas (RHAUTHAN e SCHNITZER, 1981). Estas substâncias possibilitam maior desenvolvimento das raízes em cultivos em solução nutritiva que utilizem areia como substrato (DAVID et al, 1994;AYUSO et al, 1996;e SILVA et al, 1998c). Podem ser utilizadas na produção de forragem, flores, frutas e hortaliças em sistemas de produção hidropônicos e em fruticultura, floricultura e horticultura utilizando a técnica do gotejamento.…”
Section: Mean Radius Of Root System (Cm)unclassified
“…As substâncias húmicas presentes na solução em dosagem mais elevadas apresentaram mais ligantes que os íons metálicos presentes na solução para poderem ser complexados e se tornarem menos disponíveis para as raízes das plantas, inibindo o desenvolvimento das mesmas (RHAUTHAN e SCHNITZER, 1981). Estas substâncias possibilitam maior desenvolvimento das raízes em cultivos em solução nutritiva que utilizem areia como substrato (DAVID et al, 1994;AYUSO et al, 1996;e SILVA et al, 1998c). Podem ser utilizadas na produção de forragem, flores, frutas e hortaliças em sistemas de produção hidropônicos e em fruticultura, floricultura e horticultura utilizando a técnica do gotejamento.…”
Section: Mean Radius Of Root System (Cm)unclassified
“…According to the data illustrated in the same The simulative effect of humic acid on macronutrients concentrations might be explained by David et al (1994) who indicated that humic acid enhanced cell permeability which in turn made more rapid entry of minerals into root cells and thus resulted in higher uptake of plant nutrients.…”
Section: N P K In Leaves and Podsmentioning
confidence: 99%
“…Radioisotopes were used to show that foliar-applied fertilizers passed through the leaf cuticle and into the cells [2]. Various studies have shown that a small amount of nutrients (nitrogen, potash, or phosphate) applied by foliar spraying increases significantly the yield of crops [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%